ERP Implementation Readiness Assessment at SKPD Indramayu Regency Reviewed from the Side Technology, Organization, and Environmen Using the PLS-SEM Method - Leonderson Hariyanto; R. Wahjoe Witjaksono (Eduvest - Journal of Universal Studies, 2025)
The Electronic-Based Government System (SPBE) is the core of e-Government, which aims to create a clean, transparent, and free government from corruption, collusion, and nepotism. SPBE utilizes information and communication technology to improve the efficiency and effectiveness of public services, so that it plays an important role in improving the quality of services, the implementation of government duties, and interaction with the community and inter-institutions. Enterprise Resource Planning (ERP) systems are the main tool for optimizing information management by integrating eGovernment systems for more structured problem monitoring. This research measures the readiness of ERP implementation in the local government of Indramayu Regency, with a focus on technology, organization, and environmental readiness. This research uses a quantitative approach by distributing questionnaires to 230 respondents from 5 SKPDs in Indramayu Regency. Data analysis was carried out using the PLS-SEM method through the R Study application. The results showed that of the three hypotheses developed, one was accepted with a positive and significant influence (p-value < 0.05, t-statistic > 2.045), while the other two were rejected. The technological aspect has a negative and insignificant influence on ERP readiness, the organizational aspect has a positive and significant influence, and the environmental aspect has a weak and insignificant positive influence. Improving the quality of technology and the environment is important for the successful implementation of ERP.